2020
DOI: 10.1111/add.15019
|View full text |Cite
|
Sign up to set email alerts
|

The association between recreational cannabis commercialization and cannabis exposures reported to the US National Poison Data System

Abstract: Background and Aims Recreational cannabis has been legalized in 11 states and District of Columbia (DC) in the United States. Among these, 10 states further permitted retail sale to provide a legal supply to adults. This study examined the associations of cannabis exposures with recreational cannabis legalization and commercialization. Design Secondary data analysis of state‐quarter level cannabis exposures during 2010–17 in the United States. Linear regressions with a difference‐in‐differences design were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 32 publications
3
53
0
1
Order By: Relevance
“…This finding is consistent with previous research reporting that increases in cannabis consumption were associated with laws permitting medical dispensaries but not medical laws alone, 35 and increases in poison control center calls for cannabis exposures were associated with laws permitting recreational dispensaries but not recreational laws alone. 38 Unlike homegrown cannabis sources, dispensaries imply opportunities for large-scale, profit-driven commercial markets; greater exposure to advertising; and greater access to diverse, rapidly evolving, higher-potency products. 1 , 37 In this study, the absence of dose-related product restrictions among states with recreational dispensaries was associated with larger increases in violent injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous research reporting that increases in cannabis consumption were associated with laws permitting medical dispensaries but not medical laws alone, 35 and increases in poison control center calls for cannabis exposures were associated with laws permitting recreational dispensaries but not recreational laws alone. 38 Unlike homegrown cannabis sources, dispensaries imply opportunities for large-scale, profit-driven commercial markets; greater exposure to advertising; and greater access to diverse, rapidly evolving, higher-potency products. 1 , 37 In this study, the absence of dose-related product restrictions among states with recreational dispensaries was associated with larger increases in violent injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure was a categorical variable reflecting the degree of cannabis commercialization in each state-month. We classified each state and month based on the type of law (medical or recreational) and the availability of dispensaries (commercialization) as follows 35 , 37 , 38 : (1) no cannabis legalization law (reference category), (2) medical only without dispensaries, (3) medical only with dispensaries, (4) recreational without dispensaries, and (5) recreational with dispensaries.…”
Section: Methodsmentioning
confidence: 99%
“…Most research on cannabis legalization worldwide has focused on assessments of cannabis use prevalence, and it rarely evaluates outcomes of actual cannabis-related harms or benefits. Of those studies evaluating cannabis legalization's potential harms or benefits to youth, most have focused on harms, with results indicating legalization-associated increases in (i) child and youth cannabis exposures reported to poison control centers in the US [20,21]; (ii) prevalence of cannabis-use disorders among adolescents in recreational cannabis law (RCL) states versus non-RCL states in the US [22]; and (iii) youth presentations to emergency department settings for International Classification of Diseases 10th Revision (ICD-10) cannabis-use disorder or cannabis poisoning conditions (Callaghan, Sanches, Vander Heiden, Asbridge, and Kish, unpublished data, 2020). In this regard, our study provides initial evidence of potential counterweight benefits by showing that the implementation of Canada's Cannabis Act was associated with substantial reductions in youth cannabis-related involvement with the police…”
Section: Discussionmentioning
confidence: 99%
“…One of the major concerns of those who oppose cannabis legalization in the United States is that it will increase cannabis-related harm, such as acute adverse effects of intoxication. Shi & Liang assess these concerns by comparing trends in calls to the US National Poison Data System between 2010 and 2017 in US states that either did or did not (i) legalize cannabis use and (ii) legalize retail sales of cannabis [1]. They found that legalizing cannabis use did not increase the number of calls, whereas the legalization of commercial cannabis sales did.…”
mentioning
confidence: 99%
“…These effects include: increased accidental ingestions of cannabis products (gummies and extracts) by children; unpleasant psychological experiences in adults receiving larger than intended doses of tetrahydrocannabinol (THC); and a new syndrome, cannabis hyperemesis syndrome, in heavy daily cannabis users .One of the major concerns of those who oppose cannabis legalization in the United States is that it will increase cannabis‐related harm, such as acute adverse effects of intoxication. Shi & Liang assess these concerns by comparing trends in calls to the US National Poison Data System between 2010 and 2017 in US states that either did or did not (i) legalize cannabis use and (ii) legalize retail sales of cannabis [1]. They found that legalizing cannabis use did not increase the number of calls, whereas the legalization of commercial cannabis sales did.…”
mentioning
confidence: 99%